Relação do nível de ansiedade com o estado nutricional e apoio familiar em mulheres submetidas à cirurgia bariátrica - MOURA, Dyenne Cristina da Silva (2023)
The present study aims to analyze the relationship of anxiety levels with nutritional status and family support of women undergoing bariatric surgery after 24 months of bariatric surgery. This is a crosssectional, descriptive and analytical study with convenience nonprobabilistic sampling of 18 women who underwent bariatric surgery (BC) 24 months ago or more, using Gastric Bypass or Sleeve Bypass techniques, attended by the extension project entitled "Nutritional Monitoring in Bariatric Surgery" (NMBS). The research was approved by the Ethics and Research Committee of the Institute of Health Sciences / UFPA (CAAE 59781416.0.0000.0018) and all the patients signed the Informed Consent Term. Information on sociodemographic parameters, anthropometric characteristics, eating behavior, degree and satisfaction with family support in the postoperative period were collected. For the statistical analysis of the data were used the Kruskal-Wallis, Mann-Whitney and Pearson correlation tests. In the analysis of the main components, the BIOESTAT v. 5.3, and the Exploratory Multivariate Principal Components Analysis (PCA) technique was applied. Reported having full family support 14 patients (77.8%). Regarding to satisfaction with family support, 11 (61.1%) patients were very satisfied. According to the current BMI, 14 participants (77.8%) were classified as grade I obesity. Severe anxiety was observed in 10 (55.6%) patients and moderate anxiety in 8 (44.4%). The interviewees described their relationship with food, where 11 (61.1%) classified it as a good relation. The feeling of guilt after meals was reported by 7 (38.9%) participants. There was a significant, moderate and inverse correlation of anxiety with family support in the postoperative period, so that the higher the anxiety, the lower the family support after the surgery. No significant statistical difference was detected between the anxiety and BMI groups, as well as no correlation between these variables. However, a higher frequency of severe anxiety was observed in obese women. In the analysis of main components, the first component had as the most important variables: physical activity, food relationship, satisfaction with family support and educational level, explaining 34.07% of the data variances. On the other hand, the second component had the most important variables of guilt for eating, anxiety, family support and income, accounting for 18.91% of the variances. It was possible to observe the fundamental importance of family support after BC, because it is inversely correlated with anxiety, being present in all the patients of the study, and at serious level in obese women. The main factors that explain 78.19% of the presence of obesity were physical activity, feelings of guilt after meals and schooling, being these lasting two, inversely and proportionally correlated.